Spatial distribution of hot days in north central region, Vietnam in the period of 1980-2013 - Ly, Pham Thi; Thuy, Hoang Luu Thu (Vietnam Journal of Earth Sciences, 2019)
Based on the data of daily maximum temperature in 26 meteorological stations in the North Center Region, Vietnam over the period of 1980 to 2013, the authors conducted the research on the spatial distribution of the number of hot days. The initial result shows that in general, in the north of the study area, the large number of hot days occurred in the plain, and tended to decrease westward and eastward. In the south, this number tends to increase from the west to the east. Especially, the largest number occurred in two areas: The Ma and Ca River’s valleys (Thanh Hoa and Nghe An provinces) and the coastal areas (Thua Thien Hue province), creating two heat centers in Tuong Duong district, Nghe An province and Nam Dong district, Thua Thien Hue province. References Adina-Eliza Croitoru, Adrian Piticar, Antoniu-Flavius Ciupertea, Cristina FlorinaRosca, 2016 Changes in heat wave indices in Romania over the period 1961-2015. Global and Plantary Change 146. Journal homepage: www. Elsevier.com/locate/gloplacha. Chu Thi Thu Huong et al., 2010. Variations and trends in hot event in Vietnam from 1961-2007, VNU Journal of Science and Technology, 26(3S). Climate Council, 2014a. Angry Summer 2013/2014. Accessed at http://www.climatecouncil.org.au/ angry-summer. Climate Council, 2014b. Angry Summer 2013/2014. Accessed at http://www.climatecouncil.org.au/ angry-summer. CSIRO and BoM, 2012. State of the Climate 2012.CSIRO and Bureau of Meteorology, Melbourne.Accessed at http://www.csiro.au/Outcomes/ Climate/Understanding/State-of-the-Climate-2012.aspx. D’Ippoliti D., Michelozzi P., Marino C., De’Donato F., Menne B., Katsouyanni K., Kirchmayer U., Analitis A., Medina-Ramon M., Paldy A., Atkinson R., Kovats S., Bisanti L., Schneider A., Lefranc A., Iñiguez C., Perucci C., 2010. The impact of heat waves on mortality in 9 European cities: results from the EuroHEAT project. Environ. Health 9, 37. http://dx.doi.org/10.1186/1476-069X-9-37. Gerald A. Meehl, 1992. Effect of tropical topography on global climate, Ann. Rev. Earth Planet. Sci., 20, 85-112. Hayhoe K., Cayan D., Field C.B., Frumhoff P.C., Maurer E.P., Miller N.L., Moser S.C., Schneider S.H., Cahill K.N., Cleland E.E., Dale L., Drapek R., Hanemann R.M., lkstein L.S., Lenihan J., Lunch C.K., Neilson R.P., Sheridan S.C., Verville J.H., 2004. Emissions pathways, climate change, and impacts on California. PNAS, 101(34), 12422-12427. Ho Thi Minh Ha, Phan Van Tan, 2009. Trends and variations of extreme temperature in Vietnam in the period from 1961 to 2007, VNU Journal of Science and Technology, 25(3S). IPCC, 2007: Climate Change 2007: Synthesis Report. Contribution of Working Groups I, II and III to the Fourth Assessment Report of the Intergovernmental Panel on Climate Change [Core Writing Team, Pachauri R.K and Reisinger A. (eds.)]. IPCC, Geneva, Switzerland, 104p. IPCC, 2014. Climate Change 2014: Synthesis Report. Contribution of Working Groups I, II and III to the Fifth Assessment Report of the Intergovernmental Panel on Climate Change [Core Writing Team, R.K. Pachauri and L.A. Meyer (eds.)]. IPCC, Geneva, Switzerland, 151p. Liu G., Zhang L., He B., Jin X., Zhang Q., Razaﬁndrabe B., You H., 2015. Temporal changes in extreme high temperature, heat waves and relevant disasters in Nanjing metropolitan region, China. Nat. Hazards, 76, 1415–1430. http://dx.doi.org/10.1007/s11069-014-1556-y. Manton M.J et al., 2001. Trends in extreme daily temperature in Southeast Asia Rainfall ad and the South Pacific, J. Climatol. 21. Nairn J.R., Fawcett R.J.B., 2015. Int. J. Environ. Res. Public Health 12, 227–253. http://dx.doi.org/10.3390/ijerph120100227. Nguyen Duc Ngu, 2009. Climate Change Challenges to development, Journal of Economy and Environment, No. 1. Perkins S.E., Alexander L.V., 2013. On the measurement of heat waves. J. Clim. 26, 4500–4517. http://dx.doi.org/10.1175/JCLI-D-12-00383.1. Peterson T.C., Heim Jr. R.R., Hirsch R., Kaiser D.P., Brooks H., Diffenbaugh N.S., Dole R.M., Giovannettone J.P., Guirguis K., Karl T.R., Katz R.W., Kunkel K., Lettenmaier D., McCabe G.J., Paciorek C.J., Ryberg K.R., Schubert S., Silva V.B.S., Stewart B.C., Vecchia A.V., Villarini G., Vose R.S., Walsh J., Wehner M., Wolock D., Wolter K., Woodhouse C.A., Wuebbles D., 2013. Monitoring and understanding changes in heat waves, cold waves, ﬂoods, and droughts in the United States: state of knowledge. Bull. Amer. Meteor. Soc., 94, 821–834. Pham Thi Ly, Hoang Luu Thu Thuy, 2015. Variation of heat waves in the North Central Region over the period of 1980-2013, Journal of natural resources and environment, 9, 81-89. Phan Van Tan et al., 2010. Study impact of global climate change on extreme weather phenomena and factors in Vietnam, prediction and adaptation strategies. Project final report, KC 08.29/06-10, Hanoi University of Science. Spinoni J., Lakatos M., Szentimrey T., Bihari Z., Szalai S., Vogt J., Antoﬁe T., 2015. Heat and cold waves trends in Carpathian Region from 1961 to 2010. Int. J. Climatol, 35, 4197–4209. http://dx.doi.org/10.1002/joc.4279. Toreti A., Desiato F., 2008.Temperature trends over Italy from 1961 to 2004, Theor. Appl. Climatol 91. Tran Cong Minh, 2007. Principle of meteorology and climate, Book, Public House of Hanoi National University. Tran Quang Duc, Trinh Lan Phuong, 2013. Changes of Hot day and Fohn Activities at Ha Tinh- Central Vietnam, VNU Journal of Science, Science and Technology, 29(2S). Trewin B., Smalley R., 2013.Changes in extreme temperature in Australia, 1910 to 2011. In: 19th AMOS National Conference, Melbourne, 11-13. Unal Y.S., Tan E., Mentes S.S., 2013. Summer heat waves over western Turkey between 1965 and 2006.Theor. Appl. Climatol, 112, 339–350. http://dx.doi.org/10.1007/s00704-012-0704-0. Will Steffen, 2015. Quantifying the impact of climate change on extreme heat in Australia. Published by the Climate Council of Australia Limited. ISBN: 978-0-9942453-1-1 (print) 978-0-9942453-0-4 (web).